Clearance of two organic nanoparticles from the brain via the paravascular pathway - Gu, Xiao; Song, Qingxiang; Zhang, Qian; Huang, Meng; Zheng, Mengna; Chen, Juan; Wei, Dan; Chen, Jun; Wei, Xunbin; Chen, Hongzhuan; Zheng, Gang; Gao, Xiaoling (Journal of controlled release, 2020)
The elaboration of nanotechnology offers valuable therapeutic options to overcome the blood-brain barrier and enable the treatment of brain diseases. However, to date, limit work has been done to reveal the fate of nanoparticles within the brain, which largely hinders their safe and effective applications. Here we demonstrated that the commonly-used organic nanoparticles reconstituted high density lipoprotein and poly(ethylene glycol)-b-poly(lactic acid) nanoparticles were cleared relatively fast from the brain (half-life <5 h). Notably, through various transgenic mice and pharmacological inhibition approaches, we revealed that the paravascular glymphatic pathway plays a key role (about 80%) in the brain clearance of the nanoparticles, and disclosed that microglia-mediated transportation is essential for facilitating nanoparticles elimination through the paravascular route. In addition, we witnessed a significant decline in the brain clearance of both of the nanoparticles in Alzheimer's model mice where the glymphatic system is impaired. These findings provide insightful data on the fate of nanoparticles in the brain, which would shed new light into the rational design and safe application of nanoparticles for brain drug delivery. The rHDL and PEG-PLA nanoparticles in the brain are majorly transported through microglia to the paravascular glymphatic pathway, the major route for their brain elimination. [Display omitted] •rHDL and PEG-PLA nanoparticles were cleared relatively fast from the brain.•Paravascular glymphatic pathway is the major route for brain elimination of the nanoparticles.•Microglia facilitates nanoparticles transport to the paravascular route.•Brain clearance of the nanoparticles was significantly declined under Alzheimer condition.